PREPARATION STUDY OF MAGNETITE FROM LAMPUNG AS MEDIUM FOR DENSE MEDIUM SEPARATOR WITH GRINDING-MAGNETIC SEPARATION PROCESS - Iman Kinasih Gusti, Hyang
Indonesia is a country with magnetit ore resources which is not fully utilized. Magnetit ore can be use on a several condition, one of them are to be medium in dense medium separator. One of Indonesia’s company, KPC, uses magnetite from Australia to be medium in dense medium separator. Therefore, it is needed to conduct study about preparation process of magnetite ore from Indonesia in regards to transform magnetite ore to be medium in dense medium separator. To uniform the ore characteristic is done by ore beneficiation process. In this study, concentration and size reduction are conducted using the difference of magnetic properties of Lampung magnetite ore so it would have same characteristics as Australia magnetic ore which would be medium in dense medium separator on coal beneficiation process. A series of grinding experiment was carried out to conduct study of size reduction of magnetit ore. The size reduction process was done with a variation of time milling 90 minutes, 105 minutes and 120 minutes and variations in the jar mill rotational speed 40 rpm, 50 rpm and 60 rpm. Beside that, magnetic separator experiment was also conducted to separate gangue mineral from main mineral which is Fe3O4. The best results of grinding process which meet the criteria were carried out on mineral separation process using difference of magnetic properties. The process used a magnetic separator with a variation of the current strength 0.2 A, 0.5A, and 0.8A and variations of the magnetic roll rotational speed 15 rpm, 20 rpm and 25 rpm. Based on grinding process, percentage of ore which can be passed on fraction 53 ?m at a time variation of 120 minutes and a speed of 60 rpm is 95.69%. The best percentage of magnetic content is achieved when using a variation of 15 rpm rotational speed and 0.8A current strength which is 99.13% and the largest Fe content 50.00% is reached on magnetic current 0,5 A and magnetic roll speed 25 rpm. The percentage of magnetic content and magnetite ore size of Lampung after going through the processing process which has met the standards are 99.13% and 95.69% passed 53 ?m. While the density value of 4.4796 gr/cm3 has not met the requirements so that Lampung magnetite cannot be used as a medium for dense medium separator.